المالية الاسلامية في ظل التحول الرقمي في الدول الاسلامية - صغور، مسعود; أوعيل ،نعيمة (جامعة الوادي University of Eloued, 2025)
في ظل التحولات الرقمية التي باتت لا تستغني عن التكنولوجيات الحديثة في المعاملات المالية من خلال الاعتماد على الانترنت خاصة بعد جائحة كورونا التي سرعت من وتيرة هذا التحول في الدول الإسلامية والعالم يأسره، أصبح الاعتماد على التكنولوجيا المالية كالهواتف الذكية ضرورة حتمية لتسهيل التعامل دون الحاجة الى التعاملات المادية، وعليه كان الابتكار من خلال التكنولوجيا الرقمية لزاما لتطوير المالية الإسلامية في الدول الاسلامية. In light of the digital transformations that have become indispensable to modern technologies in financial transactions through reliance on the Internet, especially after the Corona pandemic, which accelerated the pace of this transformation in Islamic countries and all the world., reliance on financial technology as smart phones, has become an imperative necessity to facilitate dealing without the need for transactions Materialism, and therefore innovation through digital technology was necessary for the development of Islamic finance in Islamic countries.
Islamic finance in light of digital transformation in Islamic countries
Keywords: التحولات الرقمية; المالية الاسلامية; التكنولوجيا المالية; الابتكار; الدول الإسلامية; digital transformations; Islamic Finance; financial technology; Innovation; Islamic countries